Radiological Diagnosis of Breast Diseases - Friedrich, Michael; Sickles, Edward A.; Adler, Dorit D. (Springer, 1997)
The book provides an authoritative and comprehensive overview of all aspects of diagnosis of breast diseases. Employing an integrated approach, all modern imaging modalities are described and their clinical usefulness critically validated. This will aid the clinician in the selection and evaluation of the various imaging methods in specific settings. Due attention is given to new aspects of interpretation of mammographic signs that are of particular interest for primary breast cancer diagnosis. The book also includes detailed information on the evaluation of the postoperative breast and on breast cancer screening by mammography. It will be of special interest to all who deal with the diagnosis and treatment of breast cancer
Keywords: Aufsatzsammlung; Radiologische Diagnostik; Krankheit; Mamma